2020
DOI: 10.3390/land9070230
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cover Crops to Reduce Loss of Soil Organic Matter in a Rainfed Vineyard

Abstract: Cover crops (CCs) minimize the loss of soil in permanent cropping systems where the soil is usually bare due to intense tillage or overuse of herbicides. The topsoil, the richer layer in soil organic carbon and organic matter (OM), is affected by water erosion. Nature-based solutions appear as a suitable option for sustainable farming. In this study, the effectiveness of two years of CC management to reduce the OM loss is evaluated in a rainfed vineyard in a rolling landscape (Huesca, NE Spain). Two sediment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 64 publications
3
43
0
Order By: Relevance
“…The lower SOM associated with CT could be a result of the lower C input associated with spontaneous vegetation incorporation, a higher mineralization rate triggered by tillage, as well as of the increased exposure of tilled soils to erosive processes [32], which are much less pronounced when vegetation is left as surface mulch. Conversely, the significant SOM accumulation under mulched treatments could have been stimulated by the combined effect of the OM input provided by seeded and spontaneous groundcovers along with the erosion/mineralization mitigation role of mulching [33,34,69].…”
Section: Effects Of Soil Management On Soil Biological Quality Indexmentioning
confidence: 99%
“…The lower SOM associated with CT could be a result of the lower C input associated with spontaneous vegetation incorporation, a higher mineralization rate triggered by tillage, as well as of the increased exposure of tilled soils to erosive processes [32], which are much less pronounced when vegetation is left as surface mulch. Conversely, the significant SOM accumulation under mulched treatments could have been stimulated by the combined effect of the OM input provided by seeded and spontaneous groundcovers along with the erosion/mineralization mitigation role of mulching [33,34,69].…”
Section: Effects Of Soil Management On Soil Biological Quality Indexmentioning
confidence: 99%
“…Consequently, this leads to a loss of soil fertility, soil quality, and loss of ecosystem services [120]. It should be noted, however, that extensive soil loss is not limited to vineyards; different authors have reported similar problems in various other crops [121][122][123][124]. Research has suggested that soil loss in vineyards is above the level that amounts to tolerable soil loss, less so for older vineyards with more organic matter content and higher bulk density in relation to younger vineyards [125] Moreover, accurately measuring soil loss in vineyards is fraught with difficulties, because different methodologies available tend to give different results.…”
Section: (Un)sustainable Agronomic Management and Resulting Soil Lossmentioning
confidence: 99%
“…Our study developed a new model by considering various indicators of different criteria of land degradation and desertification, namely, natural, human, and trend of degradation for finding areas with higher rate of degradation and measure probability of occurrence of worse step of degradation in these areas. In our model was tried that the framework of method for estimating of risk of land degradation become more reasonable than other models like MEDALUS (Kosmas et al, 1999) or risk assessment of desertification in Runiz Basin in Iran (Masoudi & Jokar, 2017). Considering that many factors which are involved in land degradation and unfortunately, currently available models, each in turn have some weak points.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean desertification and land use (MEDALUS) model (Kosmas, Poesen, & Briassouli, 1999) assesses desertification in regions by means of the environmentally sensitive areas (ESA) approach. In this method, different classes of ESA vulnerability to desertification can be evaluated using various data that allow the classification of the threat of desertification in a region.…”
Section: Introductionmentioning
confidence: 99%